2017
DOI: 10.3762/bjoc.13.41
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative and dehydrative coupling of dienoic acids and pentadienyl alcohols to form 1,3,6,8-tetraenes

Abstract: Dienoic acids and pentadienyl alcohols are coupled in a decarboxylative and dehydrative manner at ambient temperature using Pd(0) catalysis to generate 1,3,6,8-tetraenes. Contrary to related decarboxylative coupling reactions, an anion-stabilizing group is not required adjacent to the carboxyl group. Of mechanistic importance, it appears that both the diene of the acid and the diene of the alcohol are required for this reaction. To further understand this reaction, substitutions at every unique position of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Besides, the reaction of α-deuterated d - 1a (98%-D) and imine 2a delivered adduct d -( R )- 3a without deuterium losses under the catalysis of Pd/( S , S , S , S )- L1 , and a similar deuterium rate was observed for a product d -( S )- 4b catalyzed by Pd/( S )- L2 and additive A1 (Scheme c). Therefore, these results well supported that dienoic acid 1a would directly participate in the key Friedel–Crafts-type addition step via Pd(0) catalysis, and the decarboxylation of the π-allylpalladium intermediate would occur subsequently. , Moreover, the combination of ( Z , E )-dienoic acid 18 and imine 2a still provided the same chiral product ( R )- 3a with excellent stereoselectivity under the catalysis of Pd/( S , S , S , S )- L1 ; in contrast, a mixture of ( S )- 3a and ( S )- 4a (1.2:1) was obtained catalyzed by Pd/( S )- L2 (Scheme d), and apparent conversions of ( Z , E )- 18 to ( E , E )- 1a were observed under the catalytic conditions. These experiments suggested that different mechanisms would be involved for the ligand-controlled formal dienylation reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the reaction of α-deuterated d - 1a (98%-D) and imine 2a delivered adduct d -( R )- 3a without deuterium losses under the catalysis of Pd/( S , S , S , S )- L1 , and a similar deuterium rate was observed for a product d -( S )- 4b catalyzed by Pd/( S )- L2 and additive A1 (Scheme c). Therefore, these results well supported that dienoic acid 1a would directly participate in the key Friedel–Crafts-type addition step via Pd(0) catalysis, and the decarboxylation of the π-allylpalladium intermediate would occur subsequently. , Moreover, the combination of ( Z , E )-dienoic acid 18 and imine 2a still provided the same chiral product ( R )- 3a with excellent stereoselectivity under the catalysis of Pd/( S , S , S , S )- L1 ; in contrast, a mixture of ( S )- 3a and ( S )- 4a (1.2:1) was obtained catalyzed by Pd/( S )- L2 (Scheme d), and apparent conversions of ( Z , E )- 18 to ( E , E )- 1a were observed under the catalytic conditions. These experiments suggested that different mechanisms would be involved for the ligand-controlled formal dienylation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these results well supported that dienoic acid 1a would directly participate in the key Friedel−Crafts-type addition step via Pd(0) catalysis, and the decarboxylation of the π-allylpalladium intermediate would occur subsequently. 22,23 Moreover, the combination of (Z,E)-dienoic acid 18 and imine 2a still provided the same chiral product (R)-3a with excellent stereoselectivity under the catalysis of Pd/(S,S,S,S)-L1; in Scheme 3. Substrate Scope of the (E)-Selective Decarboxylative Dienylation Reaction with More Electrophiles a,b a Unless noted otherwise, reactions were carried out with dienoic acid (0.10 mmol), aldimine 2 (0.12 mmol), Pd 2 (dba) 3 (5 mol %), (S)-L3 (11 mol %), and BzOH (30 mol %) in DMF (0.40 mL) at 60 °C for 12 h under an argon atmosphere.…”
Section: Journal Of Thementioning
confidence: 99%
“…Croatt et al developed a palladium catalysed strategy that enabled the decarboxylative–dehydrative coupling of dienoic acids 99E and pentadienyl alcohols 169 or 170 at ambient temperature to give 1,3,6,8-tetraenes 171 . 66 Further studies indicated that a diene motif with each coupling partner, i.e. the acid and the alcohol, was necessary for the reaction (Scheme 53).…”
Section: Transition Metal Catalyzed Decarboxylative Transformationsmentioning
confidence: 99%
“…1,3,6,8-Tetraenes 165 were synthesized in a decarboxylative and dehydrative coupling from dienoic acids 162 and pentadienyl alcohols 163/164 (Scheme 47). 66 Differently from a typical palladium decarboxylative process, which requires an anion stabilizing group near the carboxylic moiety or a carboxylate anion, here a pentadienyl pentadienoate was successfully utilized without any assistance. This proved the need for the simultaneous presence of the dienoate and pentadienyl moieties to obtain the product.…”
Section: Scheme 46 Coupling Between Homoallylic Alkylboranes and Dienmentioning
confidence: 99%